Inducing Tolerance to Abiotic Stress in Hordeum vulgare L. by Halotolerant Endophytic Fungi Associated With Salt Lake Plants - Hosseyni Moghaddam, Mahdieh S.; Safaie, Naser; Rahimlou, Saleh; Hagh-Doust, Niloufar (Frontiers in Microbiology, 2022)
A characteristic trait of plants living in harsh environments is their association with fungal endophytes, which enable them to survive under extreme stress. Abiotic stress resistance in agro-ecosystems, particularly in arid and semi-arid regions, can be increased by inoculating these fungal endophytes on plants other than their original hosts. The present study is therefore focused on the possible role of three halotolerant endophytic fungi, i.e., Periconia macrospinosa, Neocamarosporium goegapense, and N. chichastianum, isolated from roots of salt lake plants growing in the central desert of Iran, in alleviating the adverse effects of salinity and drought stresses on barley under greenhouse conditions. To perform this experiment, a randomized block design was applied with three factors: fungi (four levels including three halotolerant endophytic species and control), salinity (three levels including 8, 12, and 16 dS/m), and drought (four levels including 100, 80, 60, 40 percent field capacity). All plants were measured for growth characteristics, chlorophyll concentration, proline content, and antioxidant enzyme activities. A three-way analysis of variance indicated that all three fungal endophytes, to varying extents, induced the barley plants' resistance to salinity and drought, and their combined effects. Additionally, we found that fungal endophytes were more effective when the barley plants were subjected to higher levels of salinity and drought. Under the stress of salinity and drought, a strong relationship between inoculation of fungal endophytes and enhancement of biomass, shoot length, chlorophyll concentration, proline content, and activity of catalase, peroxidase, and superoxide dismutase was indicated. We discussed that increased root growth, proline content, and antioxidant enzyme activity are the main physiological and biochemical mechanisms causing stress resistance in barley plants inoculated with endophytes. Our research findings illustrate that fungal endophytes have a substantial potential for increasing abiotic stress tolerance in barley plants, which can be applied in agricultural ecosystems.